HPLC Fingerprint of Solid-State Fermentation of Fugui Gutong Compound Prescription - Su, Jianshu; Tian, Pingfang; Lin, Qiang; Liu, Baining; Zheng, Laili; Ge, Xizhen (Asian Journal of Chemistry, 2013)
Aspergillus niger (E6.22) was employed for solid state fermentation of Fu-Gui-Gu-Tong (FGGT, hereafter solid state fermentation FGGT), a notable Chinese compound prescription, to attenuate its toxicity. Results indicated that the optimal spore density was 1.8 × 104 mL-1, incubation time was 7d, pH was 6.5, incubation temperature was 30 ºC. Under these conditions, paeoniflorin and total alkaloids were increased, but aconitine was decreased. Additionally, high-performance liquid chromatographic fingerprint of solid state fermentation Fu-Gui-Gu-Tong were determined and applied for monitoring the fermentation stability. The similarity index of 10 samples was 0.978, suggesting that the procedure of solid state fermentation Fu-Gui-Gu-Tong was stable in different batches. To investigate its acute toxicity, the mice was orally administered with graded doses of solid state fermentation Fu-Gui-Gu-Tong extract, the LD50 of the solid state fermentation Fu-Gui-Gu-Tong group was higher than Fu-Gui-Gu-Tong, meaning the less toxicity of solid state fermentation Fu-Gui-Gu-Tong. Hence, it is concluded that A. niger (E6.22) could alleviate the toxicity of Fu-Gui-Gu-Tong through solid state fermentation and the fermentation procedure was reliable and applicable.